The Relationship between Celiac Disease and Unexplained Infertility - Aboud , Rana S. (Iraqi Journal of Science, 2023)
To determine the relationship between celiac disease and reproductive complication, twenty five women with clinically definite unexplained infertility aged (22-35) have been investigated and compared to fifteen apparently healthy women. All the studied groups were subjected to measurement of anti-tissue transglutaminase antibodies IgA and IgG by ELISA technique and anti-endomysial antibodies IgA and IgG by IFAT technique .There was a highly significant elevation (P< 0.01) in the concentration of anti- tTG IgA Abs compared to control group, Also, there was significant elevation (P< 0.05) in the concentration of anti- tTG IgG Abs compared to control group .The results illustrated that the prevalence of anti-EMA IgA and IgG Abs were (5/25)20% and (3/25)12% respectively, and there was significant differences (P< 0.05) compared between studied groups. Frequency of HLA-DQ-8 by Real time PCR was (4/25)16% while no prevalence of HLA-DQ-2, and there was significant differences (P< 0.05) compared between studied groups. These results indicate that silent or sub- clinical celiac disease plays an important role in reproductive complication such as unexplained infertility.